A TEACHER TRAINING OF PHYSICAL EDUCATION AND THE SUPERVISED: THE POINTING AN EXAMINATION OF ACADEMIC PRODUCTION (CAPES) (Fiep Bulletin - online, 2016)
This article addresses the issue of Teacher Education in Physical Education and Supervised ratio within this training / process the light of available academic productions in the database - theses - CAPES, for the last decade. Aims to survey the productions in post - graduate studies and identify how the issue / subject is being addressed in the framework and level of these productions. The methodological dimension was based on the survey of productions about the topic through two sets of descriptors / keywords like: descriptor ( 1 ) - physical education, degree , stage , and descriptor ( 2 ) - physical education stage . The parameters available in the database, and which formed the basis for this work were title, author, academic level, institutional (in which one can infer the regional / geographic origin), keywords and abstract. The search was conducted with time constraints, concerning dissertations (both professional and academic master) and theses between 2002 and 2012.
Keywords: Physical Education. Stage. Teacher Training.